The Capacities of Muslim Societies in Promoting Human Rights Education - Mostafa Fazaeli; Fatematossadat Hagh Shenas (پژوهش تطبیقی حقوق اسلام و غرب, 2018)
Nowadays, human rights education is of great concern for the international community in promoting the respect to human rights. However, inattention to the challenges and obstacles that can encounter education process with inefficiency would cause failure in achieving the goals of education. Identification and applying effective and appropriate means according to local capacities in each region would provide the requirements to overcome the existing and perceived challenges and obstacles. Dual challenge of the discourse of religion and human rights in Muslim societies is a barrier to development of human rights education paying attention to which seems necessary in finding proper and appropriate means and mechanisms for human rights education in these societies based on their capacities. These capacities can be examined in two categories. The first category is the general capacity of Muslim communities, including non-governmental organizations, as well as academic legal clinics and the clinical education method of human rights that is recognized as an effective method to the core elements of human rights education in accordance with international documents in all societies. The second category is the specific capacities of Muslim communities which can considerably contribute to the promotion of human rights through localization of human rights clinical education, resolving the challenges meeting the university law clinics and increasing their effectiveness regarding human rights education in these societies. The present paper, through describing and analyzing mainly-library-based data, aims to investigate the quality of the function of general capacities and tries to identify and present the specific ones such as Waqf institution, mosques and the educational role of Muslim clerics.